Volume 8: Yoruba Architecture and Wall Painting. Digitaler Scan im Beier-Nachlass - Beier, Ulli (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent)
Copyright held by Iwalewahaus, CBCIU.
Keywords: Yoruba (African people); Architecture; Painting; Books; Yoruba Art; Wall Painting